Influences on the drinking of heavier drinkers: Interactional realities in seeking to 'change drinking cultures'. (29th June 2015) - Room, Robin; Callinan, Sarah; Dietze, Paul
Abstract: Introduction and Aims: 'Changing drinking culture' is a prominent goal in the Australian state of Victoria's current alcohol strategy—seeking a shift so that 'excessive drinking isn't seen as the norm'. As a social activity, there is a strong collective aspect to drinking and associated behaviour: customs within the drinking group and at the level of social worlds of drinking operate both to increase and to control drinking patterns and associated behaviours. The paper considers how risky drinkers and those in social worlds of heavy drinking experience others' expectations about drinking. Design and Methods: Using Victorian population survey responses ( n = 2092 adults who had consumed alcohol in previous year) to identify those in a social world of group drinking, and a subcategory who are also risky drinkers, the paper explores pressures on those in these categories both to drink more and to drink less, whether from family members, from work colleagues, or from friends. Results: Those who are both risky and social drinkers are much more likely than other drinkers to report pressures to drink more from friends and workmates, and even from family members, although they more often report pressures from family members to drink less than to drink more. Discussion and Conclusions: Efforts to change a drinking culture, it is argued, must take account of the collective nature of drinking and of the interplay of influences at interpersonal and subcultural levels if they are to be effective in reducing rates of heavy drinking and alcohol problems. [Room R, Callinan S, Dietze P. Influences on the drinking of heavier drinkers: Interactional realities in seeking to 'change drinking cultures'. Drug Alcohol Rev 2015]